(3GdEgdjdLIs - (3GdgGTej, GdbQTj, CHh YHO Gddg, GdUGOb, LYaQ GdUGOb Hf eMeO GdHGbQ, J (B148(3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3bGd MOKfj eMQR Hf SYjO GdfMhj HOeTb bGd MOKfj eMeO Hf CHj eSgQ HGdQedI Yf CHjg Yf LOg bGd cJH GdeaVd Hf YeQ GdLYaj Edi YHO Gddg LYaQ Hf eMeO GdUGOb jYdeg Cf CbhGeG XgQhG ef Cgd gPg GdedI jLMOhf GdQhHhHjI (B.. (3acJH CHh YHO Gddg (B...s
(3BNQgG (B:s
... (3aEjGc Cf jSJaRc TjWGf Gdhge hhShGS GdWHjYI EPG LHgJ HGdQO hONd Hjfc hHjf HGH GdELGHI (B.. (3GdaYGd ZjQ LGFQ aj MceI hdG NdGa aj YOdg (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\126s
(3GdPQjYI (B2\ (3bHd (B1902s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds